Nitrous oxide production kinetics from ammonia oxidation in the Eastern Tropical North Pacific in March/April 2018 - Claudia Frey; Xin Sun; Laura Szemberski; Karen L Casciotti; Emilio Garcia-Robledo; Amal Jayakumar; Colette Kelly; Moritz F Lehmann; Bess B Ward (PANGAEA, 2021)
In March/April 2018 during a cruise on R/V Sally Ride, SR1805, 15N-NH4+ incubations in 60mL glass serum bottles were performed to measure ammonium oxidation rates to nitrite and nitrous oxide in different depth at 3 different stations in the oxygen deficient zone (ODZ) of the Eastern Tropical North Pacific off the coast of Mexico. Water samples were collected from 30L Niskin bottles deployed with a conductivity-temperature-depth profiler (CTD, Seabird Electronics). The goal was to get a better understanding on the controls of nitrous oxide (N2O) production. The N2O production rate experiments were performed according to Bourbonnais et al. 2021 (https://doi.org/10.3389/fmars.2021.611937). Furthermore, ammonium (NH4+), nitrite (NO2-) and nitrate (NO3-) as well as N2O concentrations were determined using standard fluorometric (Holmes et al. 1999, https://doi.org/10.1139/f99-128), photometric (Strickland and Parsons 1972, hdl:10013/epic.46454.d001), chemiluminescent (Braman and Hendrix 1989, doi:10.1021/ac00199a007) and mass spectrometric techniques (McIlvin and Casciotti 2010, https://doi.org/10.4319/lom.2010.8.54), respectively. The N2O yield per nitrite produced was calculated. The archaeal ammonia monooxygenase gene subunit A (amoA) copy numbers/mL were determined using qPCR as described previously (Peng et al. 2015, https://doi.org/10.1002/2015GB005278).